2017
DOI: 10.1590/1980-5373-mr-2017-0189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urea Excess on the Properties of the MgAl2O4 Obtained by Microwave-Assisted Combustion

Abstract: In this paper, magnesium aluminate spinels were prepared by microwave-assisted combustion, using urea as fuel. In order to evaluate the effect of the urea excess used in the synthesis, its mass was added in a range of 1.0 to 2.5 times the stoichiometric amount required. The materials produced were characterized by TGA, FTIR, XRF, XRD, BET, SEM and TEM. The results demonstrated that magnesium aluminate spinel was formed in all solids, but the crystallinity degree and the specific surface area increased accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…This result is in a good agreement with Venkateswara Rao and Sunandana [17]. Carvalho et al [18] reported that the excessive amount of the combustion fuel of urea improves the crystallinity.…”
Section: Figure 1 Xrd Patterns Of the As-produced Samplessupporting
confidence: 88%
“…This result is in a good agreement with Venkateswara Rao and Sunandana [17]. Carvalho et al [18] reported that the excessive amount of the combustion fuel of urea improves the crystallinity.…”
Section: Figure 1 Xrd Patterns Of the As-produced Samplessupporting
confidence: 88%